Intrauterine infection caused by nontyphoidal Salmonella: a literature review. (2nd December 2021) - Mollo, Bastien; Hobson, Claire Amaris; Le Hello, Simon; Azria, Elie; Le Monnier, Alban; Pilmis, Benoit; Mizrahi, Assaf
Abstract: Objectives: Although nontyphoidal Salmonella infections have a prevalence of 0.2–1.8%. It is mostly described in veterinary medicine; it could be responsible for severe intra-amniotic infections in humans. The objective of this review is to describe the clinical and microbiological aspects of intrauterine infection (IUI) caused by nontyphoidal Salmonella . Methods: We reported a case analysis and subsequently conducted a systematic literature review of IUI caused by nontyphoidal Salmonella between 1966 and 2018. Results: In literature nine cases have been reported, and were confirmed by the identification of a nontyphoidal Salmonella in the biological samples. Our review reveals severe clinical presentations in pregnant women. Indeed, sepsis, spontaneous abortions, and fatal outcomes for fetuses were described in 90, 60, and 80% of the cases, respectively. The major clinical symptoms were in majority acute, with high fever, abdominal pain, metrorrhagia, and premature membranes ruptures. Nulliparity is a risk factor and the prognosis depends on the pregnancy stage. All mothers received antibiotics and their outcomes were favorable. Conclusions: Nontyphoidal Salmonella infections can be responsible for severe pregnancy complications. Considering the severe neonatal prognosis, in case of a history of diarrhea and/or sepsis, a search for this pathogen should be considered, and a preventive strategy could be discussed during pregnancy.